Research on the normativity of aesthetic judgements in film criticism. Issue 1 (1st January 2020) - Zahrádka, Pavel
ABSTRACT: Following methodological relativism, the paper reflects critically on objectivist theories of aesthetic judgement that derive its objectivity from the rules by which the judgement is made, or from ideal settings of the observer. Both theories share the assumption that the person delivering the reliable (objective) aesthetic judgement is an art critic. The critical reflection of both theories is based on pragmalinguistic analysis of film criticism, that is, on the reconstruction of the semantics and normativity of value judgements made by professional film critics.